Magnetic resonance cholangiopancreatography and its diagnostic value to detect choledocholithiasis in patients suffering mild acute pancreatitis (2014)
Introduction: acute pancreatitis is a common clinical disease that may be either mild or lethal. Forty percent of cases is of biliary origin and caused by Vater bleb obstruction by biliary mud or by gallstones. The diagnosis of acute biliary pancreatitis uses invasive methods such as retrograde endoscopic cholangiopancreatography which is associated to higher morbidity and mortality or non-invasive ones like magnetic resonance cholangiopancreatography that emerges as a diagnostic modality in the third and the fourth level centers. Methods: the diagnostic characteristics of the magnetic cholangiopancreatography were evaluated by using the historical registers of patients who were admitted to a 4th level university hospital and underwent magnetic cholangiopancreatography and retrograde endoscopic cholangiopancreatography, being the last one considered the method of reference for the evaluation. Results: magnetic cholangiopancreatography showed 97 % sensitivity and 44% specificity for the detection of choledocholithiasis, positive predictive value of 0.35 and negative predictive value of 0.99. Some of these results were lower than those documented in the international literature. Conclusions: magnetic resonance cholangiopancreatography allows capturing precise images of the biliary duct in a safe environment with no risks for the patient. This technique has a detection capacity ranging 78 to 97 % for choledocholithiasis. This result agrees with that of other studies.